(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Advancements in wireless communication systems have spurred the development of enhanced antennas to meet diverse application requirements. Ultra-wideband (UWB) technology, recognized for its broad frequency range, is crucial for enabling various wireless services, particularly within the expanding 5G network. This study compares four different Defected Ground Structures (DGS) integrated with a UWB antenna to function as a band-stop filter at lower (< 3 GHz) and higher (> 5 GHz) frequency bands, while allowing the critical frequency around 3.5 GHz to operate. The UWB planar antenna, designed on an FR-4 substrate material with a half ground plane, incorporates four distinct slots as filters from 2.7 GHz to 2.8 GHz and 5.3 GHz to 10.5 GHz to mitigate interference. Each DGS configuration’s performance was evaluated through simulation, assessing return loss, S-parameters, and radiation characteristics. Results showed that DGS Design 2 provided the best outcome, with a deep stopband centered at 3.5 GHz and minimal impact on efficiency, realized gain, and surface current. This study offers insights into optimizing DGS designs for UWB antenna applications. The antenna design and simulations were conducted using CST Microwave Studio software to enhance performance for advanced wireless communication systems.